Benefits of Imperfect Conflict Resolution Advisory Aids for Future Air Traffic Control - Trapsilawati, Fitri (2017)
Objective: The aim of this study was to examine the human–automation interaction issues and the interacting factors in the context of conflict detection and resolution advisory (CRA) systems.